PENTINGNYA PENDIDIKAN KARAKTER DALAM MEMBANGUN MORALITAS BANGSA DALAM DUNIA PENDIDIKAN - Susilawati, Samsul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
Forming the character of students is not an easy and quick effort. It requires continuous effort and deep reflection to make a series of moral decisions that have to be followed up with concrete action, so it becomes a practical and reflective. Need more time to make it becomes a habit or character of a person. Curriculum in Indonesia is still not touching this aspect of character, although there are lessons Pancasila and citizenship, but it is still a theory and not at the level applicable. Character education is character education plus, namely involving aspects of knowledge (cognitive), feeling (feeling), and action (action). Thus, without these three aspects, it will not be effective character education, and its implementation must be done in a systematic and sustainable. By giving the character education, is expected to change the paradigm of the nation's young people to be strong and have a good horizon.Keywords: Character and Character Education